Effect of photoperiod on the development of inflorescences in white Guinea yam (Dioscorea rotundata) - Shiwachi, H.; Ayankanmi, T.G.; Asiedu, Robert (Wiley, 2005)
In experiments in 2001 to 2003, 50-day-old plants of four varieties of white Guinea yam (D. rotundata) were exposed to 10 h (short-day) day length for 15 days, 14 h for 30 days or constant 24 h, with natural day length as the control. Under natural day length the male varieties flowered earlier than the female. Short day-length delayed and reduced the intensity of development of inflorescences, but the response to the 14 h and 24 h treatments differed between the varieties.